Uṣūl al-Naḥwi; Al-Qiyās dalam Rukun al-‘Illat dan al-Hukm - Fatkur Rohman; Iis Susiawati; Dadan Mardani (Universitas Muhammadiyah Gorontalo, 2022)
Isytiqa>q or derivation technique is the origin of qiya>s in Arabic, known as sarfiyah. Etymologically the word qiya>s means the same even though it comes from two root words. In terms of qiya>s means directing something that has no proof towards something that has proof, if it has the same meaning, or vice versa if it has the same meaning. Qiya>s is divided into two types, qiya>s istiqra>i and qiya>s syakli. There are four components in qiya>s, namely ashl, far', illat, and hukm. The purpose of this study is to describe Qiya>s in the pillars of 'llat and hukm. The approach and research method used is descriptive qualitative. Data collection is carried out based on existing data sources, namely the literature by reviewing and analyzing data findings with content analysis techniques, so that the data obtained can be presented in detail. As for the results, it can be concluded that 'illat and hukm are the elements that form the next qiya>s. Hukm in usul nahw has two meanings, namely hukm is the original rule in the science of nahwu which is closely related to qiyas istiqro'I; and hukm is a far'u discussion of the laws that exist in al-qaidah al-asliyah, which is called qiya>s tafsiri or qiya>s hamli, or qiya>s syaqli or qiya>s a'qli. It is proven that qiya>s al-nahwi is the fruit of qiya>s (analogy), both qiya>s istiqro'i or qiya>s interpretation.